Sex‐dependent difference in the relationship between adipose‐tissue cholesterol efflux and estradiol concentrations in young healthy humans. Issue 64 (12th July 2017) - Iqbal, Fatima; Durham, William J.; Melhem, Ayyash; Raslan, Saleem; Tran, Tony T.; Wright, Traver J.; Asghar, Rabia; Fujise, Ken; Volpi, Elena; Sidossis, Labros; Abate, Nicola; Sheffield‐Moore, Melinda; et al.
Abstract: Background: Impaired adipose tissue function and lower levels of high density lipoprotein cholesterol (HDL‐C) have been implicated in the development of vascular dementia, and metabolic diseases such as hypertension, atherosclerosis, type 2 diabetes (T2D) and metabolic syndrome. Interestingly, both the substrate fluxes in adipose tissue and HDL‐C concentration differ between men and women. Moreover, adipose tissue cholesterol efflux has been implicated in modulation of HDL‐C levels. Thus, we aimed to determine if the association between serum estradiol levels and adipose tissue cholesterol efflux is sex‐dependent. Method: We evaluated the serum estradiol levels and adipose tissue cholesterol efflux in young healthy men (n = 5) and women (n = 3). Adipose tissue cholesterol efflux was determined using subcutaneous microdialysis probes. Linear regression analyses were used to determine the relationship between the parameters, p < 0.05 was considered as statistically significant. Results: Our data demonstrated that serum estradiol levels directly associated with adipose tissue cholesterol efflux; however, the relationships may be sex‐dependent. We discussed our results in the context of currently available data regarding sex‐dependent variability in adipose tissue function and HDL‐C metabolism as a potential contributor to higher rates of vascular dementia in men. Further research is required to understand the sex‐dependent and −independent variabilities in adipose tissue metabolism to determine novel targets for interventions to prevent the development of vascular dementia.